A study of effects of supply chain relationship capital on cooperation performance under global sourcing circumstances. Issue 3 (3rd May 2016) - Li, Jieyi; Wang, Zhongming
Abstract: Based on global sourcing circumstances, 166 transnational enterprises are proceeded questionnaire survey for the effects of supply chain relationship capital on cooperation performance, and Hierarchical Regression Analysis is applied to analyze the empirical research. The research reveals the stronger tie strength, network centrality, degree of confidence, and information sharing between enterprises and suppliers, the higher cooperation performance to create win-win for both buyer enterprises and suppliers and reinforce the international competitiveness of enterprises.